A synopsis of Lauraceae (excluding Ocotea) from the Reserva Natural Vale, Linhares, Espírito Santo, Brazil - de Moraes, Pedro Luís Rodrigues [UNESP]; Vergne, Matheus Carvalho [UNESP] (Wiley, 2018)
Fifty-five species belonging to 14 genera of Lauraceae are recorded in the Reserva Natural Vale. In the present treatment, twenty-one species are reported: Aiouea (3), Aniba (2), Beilschmiedia (1), Cassytha (1), Cryptocarya (3), Endlicheria (1), Licaria (2), Mezilaurus (1), Nectandra (4), Persea (1), Rhodostemonodaphne (1), and Urbanodendron (1). Descriptions, identification keys, comments and illustrations of the species are presented. The species of Ocotea will be treated in part II of this series.
Keywords: Atlantic rainforest; Laurales; Neotropics; taxonomy